Model Discrete Wavelet Transform for Clinical IoT Data and Device Interoperability - Bezruk, V. M.; Krivenko, S. A.; Samochernov, M. B.; Kryvenko, L. S.; Krivenko, S. S. (IEEE, 2022)
The structure of a Haar Transform dataset has been examined by using pandas for machine learning aims. Statistics have been viewed with pandas and Matplotlib. Correlation between features in a dataset has been improved ten times with Model Discrete Wavelet Transform
Keywords: Wavelet Transform; dental clinic; Internet of Things (IoT); Clinical Internet of Things; Haar Transform